2020
DOI: 10.2147/opth.s265695
|View full text |Cite
|
Sign up to set email alerts
|

<p>Surgical Approaches for Implanting Xen Gel Stent without Conjunctival Dissection</p>

Abstract: The XEN Gel Stent (Allergan Inc., an Abbvie company) is an implant that lowers intraocular pressure by creating a filtration pathway from the anterior chamber to the subconjunctival space, using the same pathway as trabeculectomy. While the primary method for implantation is via ab interno approach, it is also possible to implant the device ab externo. This technique paper details the surgical steps for closed conjunctival implantation of the Gel Stent and provides surgical pearls for enhancing outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…XEN gel stent is widely implanted through ab-interno approach, however it can be successfully implanted ab-externo as well (59,62,75,82,83). Vera et al (84) have verified that both ab-interno and ab-externo approaches for XEN implantation allowed surgeons to better optimize surgery according to the patient's personal conditions, and allows customized surgery to better adapt to the surgeon's preferences. Tan et al (59), Ucar and Cetinkaya (62) and Do et al (75) reported that there were no differences in outcomes between ab-interno and abexterno approaches of the XEN implantation in terms of the IOP reduction and the success rate.…”
Section: Discussionmentioning
confidence: 99%
“…XEN gel stent is widely implanted through ab-interno approach, however it can be successfully implanted ab-externo as well (59,62,75,82,83). Vera et al (84) have verified that both ab-interno and ab-externo approaches for XEN implantation allowed surgeons to better optimize surgery according to the patient's personal conditions, and allows customized surgery to better adapt to the surgeon's preferences. Tan et al (59), Ucar and Cetinkaya (62) and Do et al (75) reported that there were no differences in outcomes between ab-interno and abexterno approaches of the XEN implantation in terms of the IOP reduction and the success rate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the findings reflect results of surgical approaches that may not represent current preoperative preparation methods, refinements in surgical techniques, and peri-and postoperative practices. The gel stent-related surgical techniques are indeed evolving rapidly, with a major emphasis on the implant's distal end being placed supra-or sub-Tenon, which can be achieved via abinterno or ab-externo approaches, with or without conjunctival dissection (Panarelli et al 2020;Vera et al 2020). Other practices, such as preoperative control of inflammation by avoiding topicals with preservatives and/or using steroids, primary needling at the time of implantation and modulation of fibrosis with a 5-fluorouracil regimen, are being incorporated into clinical practice (Lenzhofer et al 2019;Vera et al 2019;Panarelli et al 2020;Vera et al 2020;Wałek et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Two papers were recently published that detail different techniques using both ab interno and ab externo approaches, with and without conjunctival dissection. 7 , 8 The authors of this paper sought to compare the outcomes of the most commonly reported closed conjunctiva, ab interno placement technique, with an open conjunctiva, ab externo approach that has been adopted by the operating surgeon (NMR). This retrospective chart review compares the outcomes using these two different techniques.…”
Section: Introductionmentioning
confidence: 99%